MENINGKATKAN KEMAMPUAN PENGUCAPAN KONSONAN BILABIAL [B] MELALUI METODE STIMULASI VISUAL AUDITORIS KINESTETIK TAKTIL BAGI ANAK TUNAGRAHITA RINGAN - Yulinda, Tarmansyah, Kasiyati (Jurnal Penelitian Pendidikan Khusus, 2013)
Research was motivated by the problems that researchers in the field discover that a child's mild mental retardation X 3 Basic class  in SLB Wacana  Asih Padang, impaire in bilabial consonant pronunciation. Thus the researcher seeks to help improve pronunciation skills bilabial consonant [b] at the beginning, middle and end of words through auditory kinesthetic method Taktile Visual Stimulation (VAKT). Study aimed to prove that the VAKT can improve bilabial consonant pronunciation [ b] at the beginning, middle and end of words for mild mental retardation children X. The research methodology used was a single subject research (SSR) with A-B-A design the graphic and visual analysis techniques. Subjects were mild mental retardation children basic 3, measure ment variables using percentages. The results are analyzed include the number of observations in the baseline condition (A1) seven times seen the highest value reached only 10%, treatment condition (B) ten times and the highest value reached 90% and the baseline condition (A2) as much as five times the highest value achieved 100%.  Recommended for further research and classroom teachers in order to use the method to train VAKT bilabial consonant pronunciation skills in children.